PHYSIOLOGICAL EFFECTS OF QUICK CHECK AND PSYCHOLOGICAL MASSAGE AND MASSAGE PODAL VOLUNTEERS IN SPONTANEOUS SERVED BY BEAUTICIANS (Fiep Bulletin - online, 2016)
The physical and psychological stress of modern life has become a public health problem. It is observed that most people complain of muscle pain and physical exhaustion. We note also that the people are looking for methods such as massage therapy esto improve the quality of life and sense of well-being. Duet lack of time of modern life, techniques that promote physical and psychological well-being and can be performed in a short time as the Quick Massage and Massage Podal are having more and more followers. Thus, this study investigates the improvement of well-being and decreased of stress base don't he results of physiological and psychological effects of Quick Massage and Massage Podal done together. In this study were measured blood pressure and heart rate before and after performing the massages by beauticians in 30 spontaneous volunteers. It was found that there was a reduction in blood pressure and heart rate, because the touch massage and maneuvers such as slip, promoted widespread relaxation. The volunteers also completed a questionnaire indicating their stress levels before and after the massage and it was found that 97% of these had the feeling of relaxation or much relaxation.
Keywords: Physiological effects; Quick Massage; Podal Massage.